Progressive encephalopathy associated with novel compound heterozygous NAXE mutations in a Chinese patient: case report and literature review - Zhu, Yanjie; He, Peifeng; Luo, Rong; Chen, Xiaolu (Frontiers in Pediatrics, 2026)
BackgroundNAD(P)HX epimerase (NAXE) deficiency is a rare, often fatal, autosomal recessive neurometabolic disorder of early childhood, characterized by acute neurological regression triggered by febrile illness. Here, we report a case with compound heterozygous NAXE mutations (c.733A > C and c.389A > C) associated with a milder phenotype, thereby expanding the known disease spectrum.Case reportA previously healthy 19-month-old girl presented with acute neurological regression after a high-grade fever, losing motor skills and exhibiting lethargy. Initial investigations showed leukocytosis, elevated C-reactive protein, and MRI findings of sulcal/cisternal widening and spinal cord signal changes. Given the unexplained encephalopathy, whole-exome sequencing was performed, which identified compound heterozygous NAXE mutations, confirming the diagnosis. Management included intravenous immunoglobulin, corticosteroids, and NAD + precursors. Neurological improvement was observed during the hospital course, and near-complete motor recovery was achieved by the 11-month follow-up.ConclusionThis case underscores the need to consider NAXE-related encephalopathy in children with fever-induced acute neurological decline. The discovery of a novel compound heterozygous variant combination [c.389A > C [p.His130Pro] and c.733A > C [p.Lys245Gln]] defines a milder phenotypic spectrum and mandates early genetic testing for timely diagnosis and prognostic insight. Importantly, given the single-case nature of this observation, conclusion regarding treatment efficacy remains hypothesis-generating and require validation in additional cases.